Waste minimization by recycling of construction waste - Mohd Nizam, Yusoff (2010)
Growth in construction activities generates construction waste which is fast becoming a serious environmental problem with deadly consequences;. Most of the construction and demolition, waste in our country are not recycled but end up in landfills occupying valuable land.not to mention the cost incurred in landfilling. in line with this, a study on the benefits of waste minimization, the materials which could be recycled, methods used to dispose waste materials and the factors as to why recycling is not popular was carried out. The scope of study covers construction companies which are registered with. either CIDB. or PKK (Pusat Khidmat Kontraktor) the building construction industry. The study will be carry out by an interview and also series of questionnaire. Data will be analyzed using average index. From this study, the benefits of waste minimization are conservation of natural resources, increase profit, improve company image and achieve a cleaner and safer construction site. The material which could be recycled are ferrous metal, non-ferrous metal, asphalt, brick, concrete, timber, glass, masonry, paper and cardboard, plastic and fibre-reinforced polymer(FRP). The methods of 'waste disposal are landfill, dumping, open air burning, recycling, reuse and incineration.